Recovery from Adverse Effects of Heat Stress on Slow-Growing Chicks Using Natural Antioxidants Without or with Sulphate - Ali, M.N.; Qota, E.M.A.; Hassan, R.A. (International Journal of Poultry Science, 2010)
An experiment was designed to study the effect of Curcuma longa (CL), Cuminum cyminum L(CC) alone or with sulphate ion on alleviating the heat stress effects compared to vitamin C. Three hundred and sixty, 21-day old unsexed chicks of slow growing El-Salam strain were randomly divided among 8 treatments (each of 3 replicates of 15 unsexed chicks each) and housed in floor pens. One group was kept under thermoneutral condition at 28±4oC and 55±3% Relative Humidity (RH) during 21-84 day of age and fed practical corn-soybean meal diet (control diet). The other seven groups were kept for three successive days weekly under heat stress at 38±1.4oC and 49±2% RH from 12.00 to 16.00 pm. Chicks in Heat Stress treatments (HS) were fed basal diet without additives or with 250 mg Ascorbic Acid (AA) /kg diet, 0.2% of Curcuma longa (CL),0.2% Cuminum cyminum L (CC), 0.5% anhydrous Sodium Sulphate (SS), 0.2% CL+0.5%SS and 0.2%CC+0.5%SS. Heat Stress decreased body weight gain, feed intake, feed conversion, carcass percentage, nitrogen retention, ash retention and plasma antioxidants capacity while increased respiration rate (RR) and rectal temperature (RT). The addition of CL, CC alone or with SS in the diet can recover the negative effect of HS on performance, nitrogen retention, ash retention and plasma antioxidants capacity. To some extent these additives recover the negative effect on RR and RT. The Cuminum cyminum L plus sulphate seemed to be the best additive under the condition of this study.